Video Profile Pada SMK Kusuma Bangsa Kabupaten Tangerang Sebagai Penunjang Informasi Dan Promosi - Achmad Zainudin MN; Sutajaya Sutajaya; Ajeng Retno Anggraeni (UNIVERSITAS RAHARJA, 2019)
Also new is a nation deeply influenced by the quality of the human resources community of the nation. Quality of human resources depends on the level of education of each of the elements accentuate Personality-forming nation. SMK Kusuma nation has many amenities and have a way of studying the fruit. So, THIS has the advantage that Nation Kusuma is incredible, based on the results of data analysis it was concluded that the promotion of quality in the development of video through school in SMK Tangerang Bsngds Kudums implemented with good coordination involves Rukan resources are there in school so successful in making the video profile of the school (students, parents and the community) so as to provide quality educational services.